2019
DOI: 10.1097/md.0000000000017651
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis approach on diagnostic value of MLH1 promoter methylation for head and neck squamous cell carcinoma

Abstract: Background:Head and neck squamous cell carcinoma (HNSCC) is the leading histological type among head and neck cancers. Several studies have explored an association between aberrant methylation of MutL homolog-1 (MLH1) promoter and HNSCC risk. We aimed to explore the associations between MLH1 promoter methylation and HNSCC by using a meta-analysis.Methods:Systematic literature search was conducted among PubMed, Google Scholar, Web of Science, and China National Knowledge Infrastructure, and Wanfang databases to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…These differences reflect the heterogeneity of these diseases in their histology and clinical behavior, with different aetiologias and risk factors, and known tissue and tumor-type specificity of methylation patterns [ 22 ]. The prevalence of MGMT and MLH1 methylation detected in this study are also consistent with previously summarized data for HNSC in the TCGA database [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…These differences reflect the heterogeneity of these diseases in their histology and clinical behavior, with different aetiologias and risk factors, and known tissue and tumor-type specificity of methylation patterns [ 22 ]. The prevalence of MGMT and MLH1 methylation detected in this study are also consistent with previously summarized data for HNSC in the TCGA database [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…The MLH1 promoter methylation has been reported as a well-established biomarker in several types of cancer, such as esophageal cancer, colorectal cancer, non-small cell lung cancer, gastric cancer, papillary thyroid cancer, and bladder cancer [16] .…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis has suggested that hypermethylation of the MLH1 promoter is associated with HNSCC. Thus, methylated MLH1 could be a potential diagnostic biomarker for HNSCC (91). One study showed that epigenetic silencing of O6-methylguanine-DNA methyltransferase (MGMT, involved in the DR pathway) DNA repair enzyme through promoter hypermethylation (HmMGMT) may increase TP53 oncosuppressor gene mutations, thereby promoting HNSCC (92).…”
Section: Dna Damage Repair In Hnsccmentioning
confidence: 99%